Pengaruh Infrastruktur terhadap Pertumbuhan Ekonomi Provinsi Sulawesi Tengah - Moch Alfazir Subhartha; Made Kembar Sri Budhi (Universitas 17 Agustus 1945 Semarang, 2025)
Development is a planned process carried out by the government or related institutions to encourage changes that contribute to improving people's welfare. In this case, development is seen as a systematic effort to achieve people's welfare, where the government plays a strategic role in driving the wheels of development, especially in supporting economic growth. Economic growth can be driven through infrastructure development, such as roads, electricity, and mining, because all three play an important role in supporting economic and social activities. This study aims to analyze the effect of road infrastructure, electricity infrastructure, and mining infrastructure on economic growth in Central Sulawesi Province. This study was conducted in Central Sulawesi Province using a quantitative method based on secondary data. The data analysis technique used is multiple linear regression. The results of the study show that simultaneously, road infrastructure, electricity infrastructure, and mining infrastructure have an effect on economic growth in Central Sulawesi Province. However, partially, only electricity infrastructure has been shown to have a significant effect on economic growth, while road and mining infrastructure do not show a significant effect. However, the government needs to review the strategy for developing and maintaining road and mining infrastructure. Factors such as the low quality and quantity of roads and the lack of development of downstream industries for nickel processing can be obstacles that hinder the effectiveness of this infrastructure in supporting economic growth. On the other hand, increasing electricity capacity and distribution remains a priority to support the development of the industrial sector and small businesses in the region.